Evaluation of the efficacy of Tai Chi on the cognitive function of patients with mild cognitive dysfunction and research on its mechanism - Lin, Lin; He, Yao-Xi; Wen, Quan; Liu, Jia-Yang; Dai, Yu; Fei, Yu-Zhe; Li, Hang; Li, Chang-Qing; Zhou, Huan (Frontiers in Aging Neuroscience, 2025)
IntroductionStudies have revealed that Tai Chi can enhance cognitive functions among patients with mild cognitive impairment (MCI). However, the precise mechanisms underlying this improvement remain elusive.MethodsConsequently, we conducted a study involving 54 elderly inpatients with MCI residing in a combined medical and elderly care facility in Chengdu, who were randomly divided into three groups: a control group engaging in daily living activities, a Tai Chi group that performed Tai Chi exercises in addition to control group activities, and a walking group that undertook walking activities as a supplement to the control group regimen. The intervention period lasted for 24 weeks, comprising 12 weeks of exercise and an additional 12 weeks of follow-up. The Montreal Cognitive Assessment (MoCA), Trail Making Test-A (TMT-A), Auditory Verbal Learning Test (AVLT), and biochemical assessments (measuring brain-derived neurotrophic factor, BDNF, and platelet factor 4, PF4) were administered to investigate overall cognitive function, executive function, memory capacity, and changes in serum concentrations of BDNF and PF4 before, after, and during the follow-up period. Data were analyzed using IBM SPSS 26.0, with statistical methods encompassing descriptive analysis, ANOVA, rank-sum test, repeated measures ANOVA, and generalized estimating equations.ResultsOur findings indicated that after 24 weeks of intervention, the Tai Chi group exhibited improvements in cognitive function, executive function, and memory compared to the control group. This enhancement may be attributed to an increased expression of serum BDNF.DiscussionIn conclusion, our study underscores the potential of Tai Chi in ameliorating cognitive function among elderly patients with mild cognitive impairment, thereby offering significant implications for clinical prevention and treatment strategies targeting this condition.